Surgery for Otitis Media with Effusion: A Survey of Otolaryngologists Who Treat Children in Brazil - Manoel de Nobrega; Daniela Carvalho; José Faibes Lubianca Neto (International Archives of Otorhinolaryngology, 2023)
Introduction Myringotomy and ear tube placement (MTP) is the surgical treatment for otitis media with effusion (OME), and it is the most common surgery performed in children. Several guidelines have been developed to assist in the care of patients who become candidates for MTP. Objectives To evaluate the practice of Brazilian otorhinolarynogologists when performing MTP according to the years of clinical experience. Secondarily, we also want to assess if their practice regarding MTP varied according to the percentage of children treated and the location of their practice. Methods A 30-question survey was sent to otolaryngologists affiliated with the Brazilian Academy of Pediatric Otorhinolaryngology (Academia Brasileira de Otorrinolaringologia Pediátrica, ABOPe, in Portuguese) and/or the Scientific Department of Otorhinolaryngology of the Brazilian Society of Pediatrics (Sociedade Brasileira de Pediatria, SBP, in Portuguese). The questions included were carefully chosen to provide a profile about the practices adopted in the pre-, peri- and postoperative periods of MTP. Results The questionnaire was sent to 208 otolaryngologists, and there were 124 (59.6%) respondents. Of those, 59.7% use antiseptics before surgery. Only 54 otolaryngologists, less than half of the subjects in this study (43.5%), always place a tube during the procedure. More physicians who practice in small cities recommend water precautions after MTP when compared to other physicians (p < 0.001). Conclusion The present study reveals that many respondents do not follow some of the recommendations of the current guidelines of the American Academy of Otolaryngology-Head and Neck Surgery (AAO-HNS) on OME, either perioperatively and postoperatively, or regarding the option of placing a ventilation tube. This part of the care also varied depending on the respondents' work location and experience in the medical practice.